Investigation of radiation pattern and signal coverage of single element and multiple elements patch antenna - Ghafil S.F.; Kiong T.S.; Hock G.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
In recent years, numerous antenna technologies have caught much attention since they have been proved to enhance the general functions of systems. Various services are now provided by systems with manifold antennas. These systems are capable of increasing credibility of telecommunications and enhancing channel capacity remarkably. They are also able to boost link quality which could lower interference in large extents. The present study proposes implementation of two different patch antenna elements in order to enhance coverage and signal strength of the radiation pattern. Typically, one-element and three-element antennas are applied to assess radiation pattern. Thus, the present study aims to discern signal strength of antennas. It is measured applying the frequency of WiMAX frequency communication system 2.3GHz. Data analysis results of the study demonstrate that as radiation pattern enhances, the number of elements in antennas goes up. As such, it can be concluded that the number of antenna elements should be increased in order to achieve more directivity. © 2014 IEEE.